A review on recent developments in electrochemical hydrogen peroxide synthesis with a critical assessment of perspectives and strategies - Anantharaj, Sengeni; Pitchaimuthu, Sudhagar; Noda, Suguru (Advances in colloid and interface science, 2021)
Electrochemical hydrogen peroxide synthesis using two-electron oxygen electrochemistry is an intriguing alternative to currently dominating environmentally unfriendly and potentially hazardous anthraquinone process and noble metals catalysed direct synthesis. Electrocatalytic two-electron oxygen reduction reaction (ORR) and water oxidation reaction (WOR) are the source of electrochemical hydrogen peroxide generation. Various electrocatalysts have been used for the same and were characterized using several electroanalytical, chemical, spectroscopic and chromatographic tools. Though there have been a few reviews summarizing the recent developments in this field, none of them have unified the approaches in catalysts' design, criticized the ambiguities and flaws in the methods of evaluation, and emphasized the role of electrolyte engineering. Hence, we dedicated this review to discuss the recent trends in the catalysts' design, performance optimization, evaluation perspectives and their appropriateness and opportunities with electrolyte engineering. In addition, particularized discussions on fundamental oxygen electrochemistry, additional methods for precise screening, and the role of solution chemistry of synthesized hydrogen peroxide are also presented. Thus, this review discloses the state-of-the-art in an unpresented view highlighting the challenges, opportunities, and alternative perspectives. This review analyzes the recent developments of electrochemical synthesis of H2O2 in terms of both catalysts' design and evaluation perspectives while predicting the direction of future growth. [Display omitted] •Trends in 2 electron ORR and WOR catalysts are critically analyzed.•Ambiguities in evaluation perspectives are criticized and alternatives are proposed.•Fundamentals of oxygen interfacial electrochemistry is elaborated to understand the trends.•Advantages of 2 electron WOR over 2 electron ORR in H2O2 electrosynthesis is emphasized.•Need for electrolyte engineering strategies to improve productivity and selectivity is discussed.